PROCESSES OF LAND APPROPRIATION FOR LARGE-SCALE OIL PALM DEVELOPMENT IN WEST KALIMANTAN, INDONESIA/ Processos de aquisição de terra para a produção de óleo de palma em Kapuas Hulu, Indonésia/ Proses pembebasan lahan untuk perkebunan kelapa sawit di Kapuas Hulu, Kalimantan Barat - Hasudungan, Albert (2020)
This study examines the processes of negotiation through which agribusiness investors are gaining access to large areas of land for oil palm plantations within the Kapuas Hulu district of West Kalimantan in Indonesia. Kapuas Hulu is at the forefront of current oil palm expansion in Indonesia, making this a revealing case-study of current practices at Indonesia’s oil palm frontier. In their book, Powers of Exclusion, Hall, Hirsh and Li. (2011) describe the complex interplay of processes that are assembled to effectively exclude some actors from accessing land while privileging others. In Indonesia, these powers are applied to explain how investors access plantation land for a fraction of its market value. This study presents the complexities of institutional interplays among different actors that negotiate land dispossession across three village environments, each at different stages of engagement with the palm oil industry. In Kapuas Hulu, agribusiness corporations often gain land access with the support of customary elites, causing tensions within many Dayak Iban communities. Yet, informal modes of organisation, centred on the traditional longhouse social structures, also collide with the powers of exclusion, to produce sites of resistance. Como citar este artigo:HASUDUNGAN, Albert; NEILSON, Jeff. Processes of land appropriation for large-scale oil palm development in West Kalimantan, Indonesia. Revista NERA, v. 23, n. 51, p. 366-389, jan.-abr., 2020